2019
DOI: 10.1177/1469066719860076
|View full text |Cite
|
Sign up to set email alerts
|

The high-resolution mass spectrometry study of the protein composition of amyloid-like urine aggregates associated with preeclampsia

Abstract: The study of protein misfolding and post-translational processing abnormalities is a promising diagnostic approach for socially significant pathologies associated with the accumulation of abnormal forms of proteins. Recently, it was shown that amyloid-like aggregates can be observed in the urine of pregnant women with preeclampsia, which is the most severe hypertensive complication that can lead to fateful outcomes. The protein composition of urine aggregates may clarify the molecular mechanisms underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…One such approach could be based on MS-based identification of a unique urine proteomic fingerprint predicting PE. Such a protein profile includes alpha-1 antitrypsin, albumin, IgG k-free light chains, ceruloplasmin, and interferon-inducible protein 6-16 [99], later these data were supplemented by a-1-antitrypsin, complement 3, haptoglobin, and trypstatin [144]. This could be complemented by detection of increased TTR levels in body fluids [71].…”
Section: New Approaches To Pe Diagnosticsmentioning
confidence: 99%
“…One such approach could be based on MS-based identification of a unique urine proteomic fingerprint predicting PE. Such a protein profile includes alpha-1 antitrypsin, albumin, IgG k-free light chains, ceruloplasmin, and interferon-inducible protein 6-16 [99], later these data were supplemented by a-1-antitrypsin, complement 3, haptoglobin, and trypstatin [144]. This could be complemented by detection of increased TTR levels in body fluids [71].…”
Section: New Approaches To Pe Diagnosticsmentioning
confidence: 99%
“…The ability of these peptides in preeclamptic urine to bind the amyloidophilc dye Congo Red was successfully applied for clinical practice [15]. In the presence of Congo red azo-dye, the amyloid-like structures aggregate in urine [16]. It was shown that peptides of b-sheets, α1-antitrypsin (SERPINA1), complement 3, haptoglobin, ceruloplasmin, and trypstatin are most likely targets for Congo red binding [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of Congo red azo-dye, the amyloid-like structures aggregate in urine [16]. It was shown that peptides of b-sheets, α1-antitrypsin (SERPINA1), complement 3, haptoglobin, ceruloplasmin, and trypstatin are most likely targets for Congo red binding [16]. A no-invasive Congo Red Dot Paper Test for rapid identification of PE was also presented [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatography tandem-mass spectroscopy (LC-MS/MS) has been demonstrated as a very accurate, sensitive, rapid, and high-throughput analytical technique for identification, characterization, and quantitation of peptides and proteins. [1][2][3] Mass spectra of peptides acquired by LC-MS/MS usually contain a wealth of useful information about the protonated peptides and the related fragment ions, which can be utilized to deduce the chemical structures of the fragment ions, to decipher the peptide sequences, and to figure out the presence of the post-translational modifications. 2 Mass peak patterns of peptide/protein ions are known to be significantly dependent upon their sequences and gas-phase basicity of the amino acid residues.…”
Section: Introductionmentioning
confidence: 99%